Mycophenolic acid attenuates the tumour necrosis factor‐α‐mediated proinflammatory response in endothelial cells by blocking the MAPK/NF‐κB and ROS pathways. (14th November 2013) - Olejarz, Wioletta; Bryk, Dorota; Zapolska‐Downar, Danuta; Małecki, Maciej; Stachurska, Anna; Sitkiewicz, Dariusz
Abstract Background Mycophenolate mofetil (MMF) has beneficial effects in cardiac transplant patients beyond the suppression of tissue rejection. Moreover, mycophenolic acid (MPA), its active metabolite, has been associated with positive effects on atherosclerosis in animal models. The attachment of leukocytes to the vascular endothelium and the subsequent migration of these cells into the vessel wall are early events in inflammation and atherosclerosis. The aim of this study was to investigate the effects of MPA on tumour necrosis‐α (TNF‐α)‐induced, endothelial cell proinflammatory responses and the underlying mechanisms. Methods and Results Human aortic endothelial cells (HAECs) were treated with different concentrations (primarily 50 μM) of MPA before treatment with TNF‐α. The surface protein and mRNA expressions of intercellular adhesion molecule‐1 (ICAM‐1) and vascular cell adhesion molecule‐1 (VCAM‐1) were determined by flow cytometry and real‐time RT–PCR, respectively. Adhesion of leukocytes to TNF‐α‐treated HAECs was evaluated by an adhesion assay. Activation of mitogen‐activated protein kinase (MAPK) and nuclear factor‐κB (NF‐κB) was evaluated by measuring the levels of their phosphorylation using flow cytometry. NF‐κB p65 translocation was detected by Western blotting. The production of reactive oxygen species (ROS) was determined by reduction in fluorescent 2′, 7′‐dichlorofluorescein diacetate (H2 DCFH‐DA). MPA significantly inhibits TNF‐α‐induced ICAM‐1, VCAM‐1 surface protein and mRNA expression as well as adhesion of mononuclear leukocytes to HAEC. ICAM‐1 and VCAM‐1 expressions were also reduced by antioxidants such as pyrrolidine dithiocarbamate, diphenylene iodonium and apocynin. MPA inhibited TNF‐α‐stimulated ROS generation similarly to apocynin. TNF‐α increased ICAM‐1 and VCAM‐1 expression via c‐Jun NH2‐terminal kinase (JNK), extracellular signal‐regulated kinase (ERK1/2) and p38 MAPK. MPA and apocynin inhibited TNF‐α‐induced phosphorylation of all three MAP kinases. Furthermore, TNF‐α‐induced NF‐κB activation was attenuated by SP600125 (JNK inhibitor), PD98059 (ERK1/2 inhibitor, SB203580 (p38 MAPK inhibitor) and MPA. MPA also inhibited TNF‐α‐induced nuclear translocation of NF‐κB p65. Conclusion These results suggest that, in addition to the prevention of rejection, MPA may be a promising approach for the treatment of inflammatory vascular disease.